Flavonoid‐Derived Human Phenyl‐γ‐Valerolactone Metabolites Selectively Detoxify Amyloid‐β Oligomers and Prevent Memory Impairment in a Mouse Model of Alzheimer's Disease. Issue 5 (16th January 2020) - Ruotolo, Roberta; Minato, Ilaria; La Vitola, Pietro; Artioli, Luisa; Curti, Claudio; Franceschi, Valentina; Brindani, Nicoletta; Amidani, Davide; Colombo, Laura; Salmona, Mario; Forloni, Gianluigi; Donofrio, Gaetano; et al.
Abstract : Scope: Amyloid‐β oligomers (AβO) are causally related to Alzheimer's disease (AD). Dietary natural compounds, especially flavonoids and flavan‐3‐ols, hold great promise as potential AD‐preventive agents but their host and gut microbiota metabolism complicates identification of the most relevant bioactive species. This study aims to investigate the ability of a comprehensive set of phenyl‐γ‐valerolactones (PVL), the main circulating metabolites of flavan‐3‐ols and related dietary compounds in humans, to prevent AβO‐mediated toxicity. Methods and results: The anti‐AβO activity of PVLs is examined in different cell model systems using a highly toxic β‐oligomer‐forming polypeptide (β23) as target toxicant. Multiple PVLs, and particularly the monohydroxylated 5‐(4′‐hydroxyphenyl)‐γ‐valerolactone metabolite [(4′‐OH)‐PVL], relieve β‐oligomer‐induced cytotoxicity in yeast and mammalian cells. As revealed by atomic force microscopy (AFM) and other in vitro assays, (4′‐OH)‐PVL interferes with AβO (but not fibril) assembly and actively remodels preformed AβOs into nontoxic amorphous aggregates. In keeping with the latter mode of action, treatment of AβOs with (4′‐OH)‐PVL prior to brain injection strongly reduces memory deterioration as well as neuroinflammation in a mouse model of AβO‐induced memory impairment. Conclusion: PVLs, which have been validated as biomarkers of the dietary intake of flavan‐3‐ols, lend themselves as novel AβO‐selective, candidate AD‐preventing compounds. Abstract : Circulating phenyl‐valerolactone‐based metabolites, derived from cocoa and other flavan‐3‐ol‐rich foods through combined, microbial and human cell‐mediated bioconversion, selectively detoxify amyloid‐β oligomers, the most proximal causative agents of Alzheimer's disease.